Research on farmers’ willingness to grow high-quality rice based on the TAM-TPB model: evidence from China - Zhang, Bin; Cai, Yingshu; Hu, Zhen; Xie, Ning; Li, Jianfu (Frontiers in Nutrition, 2025)
IntroductionProfessional grain farmers play a key role in China’s food production, and growing high-quality rice is essential to secure their income. Existing studies have analyzed the willingness of farmers to adopt new rice varieties from a number of perspectives, such as farm characteristics and external factors, and have focused on the overall category of farmers. There are few studies to explore how professional grain farmers induce the planting intention of high-quality rice from the level of subjective psychological mechanism.MethodsBased on the Technology Acceptance Model-Planning Behavior Theoretical Framework (TAM-TPB), we used the survey data of 660 professional grain farmers in Jiangxi Province, China, and used the structural equation model to explore the influencing factors of the willingness of professional grain farmers to plant high-quality rice, and combined with the multi-group analysis method, we further discussed the differences between different groups.Results and discussionThe results indicate that the willingness of occupational grain farmers to cultivate high-quality rice is primarily positively influenced by perceived ease of use, perceived usefulness, behavioral attitudes, subjective norms, and perceived behavioral control, with perceived behavioral control having the most significant impact, followed by perceived usefulness. Perceived usefulness positively affects the willingness to grow high-quality rice through behavioral attitudes, while perceived ease of use indirectly influences this willingness via both behavioral attitudes and perceived behavioral control. The multi-group analysis reveals that high-endowment occupational grain farmers exhibit stronger effects of behavioral attitudes and perceived behavioral control on their willingness to grow high-quality rice, whereas low-endowment occupational grain farmers are more significantly influenced by subjective norms and perceived ease of use. Based on these findings, relevant authorities should establish effective communication networks with farmers, enhance their training and education on new varieties and technologies, and refine policy design to promote the willingness of farmers to cultivate high-quality rice.